Profesionalisme Guru Agama Islam: Sebuah Upaya Peningkatan Mutu melalui LPTK - Nasir, Muhammad (Dinamika Ilmu: Jurnal Pendidikan, 2013)
Ideal and professional profiles of teachers who are able to perform the task of teaching and education. That is to face the challenges in present and in the future . The expected professional teacher of Islamic studies (PAI) are: a) who has four main competencies pedagogic competence, professional, social, and personal competence , b ) who has expertise inIslamic studies and c ) a teacher of Islamic education (PAI ) which are not only experts in a variety of teaching methods but also an expert in applying the methods of education. Required Education and Workforce Education Institutions (LPTK) professional and ideal anyway. Among the traits LPTKs question is : a) has a professional lecturer in the field, b) has a curriculum that distinguishes between prospective teachers of religion in general secondary school ( high school ) and prospective teachers in certain subject areas Madrasah. c) provide lecture material is not merely theoretical but balanced with practical lectures, d) providing training and skills to prospective teachers in terms of how the process of development, implementation and evaluation of curriculum. e) provide expertise with the methods of teaching and educational methods in a balanced manner. f) should be able to produce the prospective teachers of Islamic Education (PAI) is not only an expert in the implementation of the curriculum, but also have an understanding and ability in developing and evaluating curriculum. g) must can produce the future teachers of Islamic Education (PAI) which has four domains as a whole, namely cognitive, affective, psychomotor and value.